Shaping the space : teaching the arts in lower secondary years - Paris, Lisa; Lowe, Geoffrey; Gray, Christina (Drama educator); Perry, Angela (Dance educator); Warwick, Lara (Emerald Publishing Limited : IAP | Information Age Publishing, Inc., 2024)
"There is growing recognition of the value of the Arts in helping shape understandings and capabilities for life essential for meeting the challenges of the 21st century. Consequently, in Australia, the Arts are now mandated for all students from kindergarten to year 9. In the lower secondary setting, this has led to a high demand for educators with specialised teaching skills and knowledge, as well as Arts practice skills. However, a shortage of specialised Arts educators has resulted in many teaching outside their areas of specialisation. Much of the material presented here in Shaping the Space draws upon long-established discipline-based practices but also acknowledges the considerable innovations that have unfolded in the last five years, especially in terms of pedagogy. Importantly, few individual Arts texts have drawn together key concepts within each discipline while locating each within overarching Arts practice. The text offers educators broad insights into the place of each discipline in life along with its key educational philosophies before burrowing down into practice-lead approaches to planning, teaching and assessing. We have deliberately chosen this approach rather than discrete discipline sections to allow educators to gain insights into what makes each Arts discipline unique but also part of an Arts 'whole'. Accordingly, there are five chapters on each discipline, interwoven as follows: the place of each discipline in contemporary life, key educational philosophies underpinning each discipline, planning to teach the discipline, teaching the discipline, and assessment within the discipline Educators can engage specifically with their discipline by skipping to each discipline chapter or read more generally across the various disciplines. By arranging the material this way each chapter has content that is specific to the individual discipline while offering broader engagement with similar principles across Arts practice as a whole. Whilst intended as scholarly work, we have chosen to forgo the usual academic format in favour of accessibility. References for each discipline chapter appear at the end of the topic / module rather than at the end of the text as a whole. As such, the text attempts to be more relational and reflexive to student needs and interests, more innovative and aligned to contemporary learning principles, and written in simple plain English framed around practical solutions to common Arts education challenges and demands"--